2019
DOI: 10.1080/21556660.2019.1619571
|View full text |Cite
|
Sign up to set email alerts
|

The influence of SLC22A1 rs622342 and ABCC8 rs757110 genetic variants on the efficacy of metformin and glimepiride combination therapy in Egyptian patients with type 2 diabetes

Abstract: Background: The incidence of Type 2 Diabetes Mellitus (T2DM) in Egypt is considered one of the highest in the world. Metformin and Sulfonylureas are usually prescribed together due to their efficacy and their relatively low cost. Organic cation transport 1, encoded by SLC22A1 gene, is the main transporter of metformin into hepatocytes, which is considered metformin site of action. Sulfonylureas enhance insulin release from pancreatic B- cells through bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, Naja et al [ 29 ] showed that Lebanese carriers of the AC or the AA genotype exhibited better glycaemic control in individuals with T2DM undergoing metformin/SU combination therapy. Similar effects were observed among Egyptian patients of T2DM [ 34 ]. These findings warrant the use of this polymorphism as a predictor of metformin/SU efficacy among patients of African origin with T2DM.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, Naja et al [ 29 ] showed that Lebanese carriers of the AC or the AA genotype exhibited better glycaemic control in individuals with T2DM undergoing metformin/SU combination therapy. Similar effects were observed among Egyptian patients of T2DM [ 34 ]. These findings warrant the use of this polymorphism as a predictor of metformin/SU efficacy among patients of African origin with T2DM.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, Umamaheswaran et al, who studied rs622342 on Indian population, showed that AA patients had a 5.6 times better chance to respond to metformin treatment when compared to CC patients [ 20 ]. Similarly, Reséndiz et al, who studied rs622342 on Mexican population, showed that CC genotype is significantly associated with an increase in HbA1c levels during the follow-up period [ 21 ], and Ebid et al showed in an Egyptian population that carriers of the A allele of rs622342 were more responsive to metformin in combination therapy than C allele carriers [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…That number was predicted to be doubled by 2045, and Egypt will climb to number 6th rank in the top 10 list. 8,9 There are no formal referral systems in the ministry of Health of Egypt in a delivery system, and most patients with diabetes are either treated in the private clinics through out-of-pocket fee for service, in the limited number of academic hospitals, or in the scarce dedicated diabetes centers in Cairo and some other major hospitals. According to the IDF, the current spending on diabetes in Egypt is among the lowest in the Middle-East and North Africa (MENA) at $116 per patient per year.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is also the major cause of end-stage renal disease (ESRD) and leg amputation in Egypt. 9 Therefore DM progression and complication control are some of the important components for DM management in healthcare programs. 10…”
Section: Introductionmentioning
confidence: 99%